Modelling diameter distributions of birch (Betula alba L.) and pedunculate oak (Quercus robur L.) stands in northwest Spain with the beta distribution - Gorgoso Varela, J.J:=700 1 Rojo Alboreca, A.; Afif Khouri, E.; barrio Anta, M.
(Es, En)
Ilus., 46 ref.
Keywords: BETULA ALBA; QUERCUS ROBUR; DISTRIBUCION GEOGRAFICA; DIAMETRO; ESPAÑA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES